2020
DOI: 10.1371/journal.pone.0230963
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the spatiotemporal differences and influencing factors of green water use efficiency of Yangtze River Economic Belt in China

Abstract: Combining freshwater consumption and wastewater emissions into a unified analysis framework and utilizing the epsilon-based measure (EBM) model with the characteristics of radial model and non-radial model, this paper evaluates green water use efficiency (GWUE) of 11 provincial-regions in the Yangtze River Economic Belt (YREB) and investigates its spatiotemporal differences during the period 2005-2014, on basis of which the contribution rate of each input-specific green water use inefficiency in the overall gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It also set the goal of carbon peak by 2030 and carbon neutral by 2060, which demonstrates China’s determination to achieve high-quality coordinated development featuring green, low-carbon and circular development [ 13 ]. In view of this, scholars have paid extensive attention to green development and conducted a large number of relevant studies [ 14 35 ]. Here, we mainly summarize and review green development from the following two aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It also set the goal of carbon peak by 2030 and carbon neutral by 2060, which demonstrates China’s determination to achieve high-quality coordinated development featuring green, low-carbon and circular development [ 13 ]. In view of this, scholars have paid extensive attention to green development and conducted a large number of relevant studies [ 14 35 ]. Here, we mainly summarize and review green development from the following two aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guo et al demonstrated that ER showed a significantly negative effect on regional green growth performance and technological innovation had a positive impact on regional green growth performance [ 25 ]. Overall, the majority of studies employed regression analysis method, such as spatial autoregressive models [ 24 ], panel vector autoregressive models [ 18 ], multiscale geographical weighted regression [ 17 ], spatial regression [ 21 ], spatial Durbin models [ 34 ] and random-effect panel Tobit models [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also a fundamental requirement for regional development and construction. The level of population density not only affects the rate of energy consumption and labor costs in a region but also has implications for the transformation and upgrading of local industries, ultimately influencing green development [ 55 ]. This paper compares the total year-end resident population with the area of the jurisdiction, with logarithmic treatment.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The traditional DEA model is characterized with radial and oriented measurement, and it ignores the slack variables [27,35]. Avkiran and Rowlands (2008) [36] considered that although the non-radial and non-oriented SBM model can avoid the shortcomings, the traditional radial and oriented DEA model may overestimate the regional environmental efficiency.…”
Section: Epsilon-based Measure Modelmentioning
confidence: 99%